The natural world of Lewis and Clark - Dalton, David A. (University of Missouri Press, 2008)
"Dalton reexamines many of Lewis and Clark's discoveries, and their identification of new plants and animals, in the light of modern science to show their lasting biological significance. In clear, readily accessible terms, he relates the Expedition's observations to principles of ecology, genetics, physiology, and animal behavior"--Provided by publisher.